Fraud and Misconduct in Clinical Research: A Step to Improve Ethical Practice in Research - Al-Mawali, Adhra; Idikula, John; Daniel Pinto, Avinash (Journal of Contemporary Medical Sciences, 2018)
Strict compliance to ethical principles in conducting clinical research is mandatory to ensure safety and wellbeing of study participants and legal protection of researchers. Many instances of fraud and misconduct are reported in world literature that has harmed clients and also eroded the trust that society had on bioscience researchers. In the light of a review of international experience on ethical practice in clinical research, we prepared the ‘Guideline for Responsible Conduct of Clinical Studies and Trials’ which covers important aspects of clinical research including protection of the rights, safety, wellbeing and autonomy of study participants; role and responsibilities of the researchers, supervisors and sponsors including pharmaceutical agencies; documentations required; reporting of research findings and related issues. Clinical researchers must acquire and apply knowledge, attitude and skill in conducting ethically sound high quality clinical research as prescribed in this Guideline. This review and our Guideline will hopefully be useful resources to all researchers worldwide.